Microcirculation and parenchyma of the liver in a model of acute pancreatitis using different doses of sodium tau-rocholate - Zinenko , D.Yu.; Tverdokhlib , I.V.; Zinenko , M.D. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. The development of acute pancreatitis is not limited to isolated damage to the pancreas. After creating models of acute pancreatitis using various substances that enhance the secretion of the gland, have a toxic or local activating effect, the researchers showed their dose-dependent effect. The question of the reaction of the hepatic microcirculation system during the development of acute pancreatitis, as well as their pathogenetic significance in the development of pathomorphological changes in the pancreas and liver in most aspects remains open. Objective. The purpose of the current study was to define the role of the hepatic mircocirculation in development of ultrastructural parenchymatous-stromal changes of the liver in a model of acute pancreatitis using different doses of sodium taurocholate. Methods. The variants of acute pancreatitis model were used with injection 50 mkl 1%, 2,5% and 5% solutions of sodium taurocholat into rat pancreatic duct. The morphological research of liver were carried out in 1, 4, 8, 12, 24, 48 and 72 hours after initiation of inflammation. Results. The visible reaction of hepatic mircocirculation in the experimental model of acute pancreatitis was depended on character of pathomorphological changes in pancreas. This reaction demonstrated the phase character including: 1) activation of hepatic circulation, first of all in portal component, against a background of pancreatic enzyme toxemia; 2) development of inflammatory, dystrophic, destructive and necrotic changes in hepatic parenchyme together with mircocirculation disorders against a background of pancreatic necrotic toxemia; 3) recovery and adaptation or decompensation processes in mircocirculation system of liver and hepatic parenchyme depending on the degree of pancreatogenic toxemia|. Conclusion. Within 72 hours of the experiment, at the lowest and middling doses of sodium taurocholate, in the context of reduction of acute pancreatitis, there is a gradual renovation of the structure of the microvessels and normalization of the microcirculation of the liver. In the maximum doses (5% solution) sodium taurocholate cause degradation of the liver microvessels with the progression of hemorrhages, slit red blood cells and platelet aggregation, which causes blockage of the microcirculation and the development of necrotic changes in the hepatic parenchyma.